Evaluation of Plant Growth Promoting Rhizobacteria as a Protecting Agent Against Cucumber Mosaic Virus and Chilli Veinal Mottle Virus on Chillipepper - MUHAMMAD TAUFIK; SRI HENDRASTUTI HIDAYAT; GEDE SUASTIKA; SIENTJE MANDANG SUMARAW; SRIANI SUJIPRIHATI (Bogor Agricultural University, Indonesia, 2005)
This study was conducted to evaluate the effectiveness of plant growth promoting rhizobacteria (PGPR) in protecting chillipepper plant from infection of cucumber mosaic virus (CMV) and chilli veinal mottle virus (ChiVMV). Seven isolates of PGPR, i.e. BC1, BTP2H, BTP3G, BTP3O BTP1, BTP2D, and T1F were applied as seed treatment and soil drench. Plants height, number of branch, and fruits weight were measured every one and ten weeks after virus inoculation. Virus concentration in plants and disease incidence were confirmed by enzyme-linked immunosorbant assay (ELISA). Results showed that inoculation with PGPR improved the seed germination. Eight days after sowing, the percentage of PGPR treated seed germination reached 50-84%; whereas those of untreated seed reached only 18%. In general, PGPR treatment significantly reduced (p < 0.05) the effect of virus infection on plant growth. Two PGPR isolates, i.e. BTP1 and BTP2H, maintained fruit weight of infected plants as good as those of healthy plants. Based on ELISA, PGPR was able to inhibit the disease incidence. The BTP3O and BTP2D isolates even protected the plant from ChiVMV infection. Concentration of salicylic acid and peroxidase were relatively higher on plants treated with PGPR than those without PGPR treatment. This gave an indication that PGPR may act as induction agents for systemic acquired resistance. Therefore, PGPR treatment is a promising strategy to control viral diseases on chillipepper.